Optimization of management processes in central government bodies through the integration of artificial intelligence - Bashuk, Alla; Chechel, Oleh (Eastern-European Journal of Enterprise Technologies, 2024)
The primary object of analysis in this study is the impact of artificial intelligence (AI) on various departments of a district state administration. The problem addressed by the research was to evaluate the key benefits and challenges of using AI to optimize management processes. The results demonstrated a significant increase in the efficiency of handling citizen inquiries, reducing the processing time from seven days to two days, indicating the high productivity of the implemented systems. These results can be explained by the application of automating routine tasks and optimizing workflows, which lead to the rapid processing of inquiries and reduction of administrative burdens. Moreover, the increased internal consistency of the data, confirmed by Cronbach's alpha, indicates the reliability of the metrics and assessment tools used. The distinctive features of the results, such as high transparency and efficiency of processes, became possible through the integration of the latest AI technologies, which helped solve the identified problem. These features allow AI to serve as an important tool in public administration reform. The scope of practical application of the results includes the use of AI to enhance the quality of public services and optimize internal processes in public administration. Owing to the implementation of best practices in data management and cybersecurity, departments can achieve better interaction and efficiency, promoting the development of a transparent and effective management system. The practical application of the proposed innovations could significantly improve the quality of interaction with citizens, ensuring greater satisfaction with services and compliance with modern efficiency requirements